Preparation and validation of theoretical-illustrative e-book on pelvic endometriosis: Assessment of learning and diagnostic sensitivity associated with the surgical approach - Almeida , Rafaela Veras de; Brito , Marcus Vinicius Henrique; Yasojima , Edson Yuzur (Seven Editora, 2023)
In Endometriosis is a chronic gynecological disease characterized by the anomalous implantation of endometrial tissue outside the uterine cavity, which may compromise pelvic and distant organs. It is estimated that about 5 - 20% of the world's female population has the disease in question. Clinically, it is characterized by infertility and pelvic pain, among other symptoms, and the treatment must be multidisciplinary, depending directly on clinical staging and imaging tests. The aim of this study was to construct and validate a theoretical-illustrative e-book on radiological and surgical aspects of pelvic endometriosis. The study was conducted in two stages: instrument construction and product validation. To determine content validity, a minimum Content Validity Index (CVI) of 0.80 was considered acceptable. The overall CVI result obtained was 0.957, indicating high validity of the e-book. The "Structure and Presentation" criteria obtained a CVI of 0.952 and 0.923, respectively, demonstrating good validity in these aspects. The topic "Objectives" obtained the maximum score of CVI (1.000), indicating a complete approval in this criterion. the e-book was prepared and validated according to the established criteria. The creation of a practical product, containing direct information about the diagnostic and surgical aspects of endometriosis, has been shown to have a positive impact on learning and updating knowledge in this area. DOI:https://doi.org/10.56238/ptoketheeducati-001